Waste heat driven turbo-compression cooling - Garland, Shane Daniel, author; Bandhauer, Todd M., advisor; Marchese, Anthony J., committee member; Carlson, Kenneth H., committee member (Colorado State University. Libraries, 2018)
Waste heat recovery systems utilize exhaust heat from power generation systems to produce mechanical work, provide cooling, or create high temperature thermal energy. One waste heat recovery application is to use the exhaust heat from a Natural Gas Combined Cycle Power Plant (NGCC) to drive a heat activated cooling system that can offset a portion of the plant condenser load. There are several heat activated cooling systems available including absorption, adsorption, ORVC, and ejector, but each has disadvantages. One system that can overcome the disadvantages of typical heat activated cooling systems is a turbo-compression cooling system (TCCS). In this system, the exhaust heat enters an organic Rankine cycle at the boiler and vaporizes the fluid that passes through a turbine. The turbine power is directly transferred to a compressor via a hermetically sealed shaft that is made possible by a magnetic coupling. The compressor operates a vapor-compression system which provides a cooling effect in the evaporator. The hermetic seal between the turbine and compressor allows for two separate fluids on the power and cooling cycles, which maximizes the efficiency of the turbine and compressor simultaneously. This study presents a thermodynamic modeling approach that makes system performance predictions for the baseline design case, and for off-design performance conditions. The off-design modeling approach uses turbo-compressor performance maps and a heat exchanger UA scaling methodology to accurately simulate system operation for a broad range of temperatures and cooling loads. A 250 kWth cooling capacity TCCS was constructed and tested to validate the modeling approach. The test facility simulates a 138:1 scaled NGCC power plant configuration in which the TCCS extracts 106°C waste heat from the flue gases and produces a cooling effect that offsets a portion of the NGCC condenser load. The design target for the test facility was to achieve a COP of 2.1 while chilling water from 17.2°C to 16°C at an ambient temperature of 15°C. Although the final design point was not tested for this study due to facility limitations, the off-design performance methodology was utilized to predict the performance for an ambient condition of 27.5°C and power and cooling cycle mass flow rate range between 0.35 kg s-1 - 0.5 kg s-1 and 0.65 kg s-1 – 0.85 kg s-1, respectively. The comparison between the experimental and modeling data suggested strong correlation over the data range presented with a maximum error in COP of only 2.0% among the selected data points. Future experimental data over a larger range of ambient temperatures and system conditions is suggested to further validate the system modeling. Regardless, the results in the present study show that the TCCS compares favorably with other heat activated cooling systems.
Keywords: off-design performance modeling; thermodynamic system modeling; waste heat recovery; power plant cooling; coefficient of performance; turbo-compression cooling